Effect of recombinant human erythropoietin in a rat model of moderate chronic renal failure – focus on inflammation, oxidative Stress and function/renoprotection - Garrido, P. (2010)
Background/Aims: Chronic renal failure (CRF) patients develop anaemia, thus promoting cardiovascular complications, which seems to be favoured by the low kidney erythropoietin (EPO) production. The renal insufficiency degree might determine the moment to start recombinant human EPO (rhEPO) therapy. It has been attributed important non-hematopoietic effects to rhEPO, which might underlie cardio and renoprotection. This work aimed to evaluate the effect of rhEPO in a rat model of moderate CRF, focusing on inflammation, oxidative stress and function/renoprotection. Methods: Four groups (n=7) of male Wistar rats were evaluated during a 15 week follow-up period: control (without treatment); rhEPO (50 IU/Kg/wk Recormon®); CRF and CRF+rhEPO. Blood samples were collected at the beginning and 3, 9 and 12 weeks after 3/4 nephrectomy, in order to evaluate: renal function, haematological parameters, iron metabolism and serum proliferative (TGF-B1), inflammatory (TNF-a, CRP, IL-2 and IL-1B) and redox status (MDA, TAS and 3-NT) markers. Kidney gene expression of Il2, Vegf, Nos2 and Nos3 were assessed by real-time PCR. Blood pressure, heart rate and tissues trophy indexes were also estimated. Results: Our data are consistent with a sustained moderate degree of CRF with development of moderate and corrected anaemia and hypertension. The remnant kidney showed a proliferative profile, with increased mass (hypertrophism), upregulated tissue Vegf gene expression, accompanied by increased levels of serum TGF-B1. Serum 3-NT was augmented, suggesting oxidative stress, which was accompanied by a trend to higher kidney Nos gene expression of both isoforms. rhEPO treatment was able to partially attenuate renal function markers, totally correct anaemia, also demonstrating a proliferative and antioxidant action, suggesting renoprotection. Conclusion: This study suggests that rhEPO therapy might be recommended in moderate CRF stages in order to efficiently correct not only the anaemia but also the underlying deleterious mechanisms, due to a proliferative and antioxidant action on the remnant kidney.